Khrushchev : the man and his era - Taubman, William (New York : Norton, 2004)
Tells the life story of twentieth-century Soviet leader Nikita Khrushchev, featuring information from previously inaccessible Russian and Ukrainian archives.
The Fall: October 1964 -- Kalinovka's Own 1894-1908 -- Making it as a metalworker: 1908-1917 -- To be or not to be an Apparatchik: 1918-1929 -- Stalin's Pet: 1929-1937 -- Stalin's Viceroy: 1938-1941 -- Khrushchev at War: 1941-1944 -- Ukrainian Viceroy Again: 1944-1949 -- The Heir Nonapparent: 1949-1953 -- Almost triumphant: 1953-1955 -- From the secret speech to the Hungarian Revolution:1956 -- The Jaws of Victory: 1956-1957 -- The Wider World: 1917-1957 -- Alone at the top: 1957-1960 -- The Berlin Crisis and the American Trip: 1958-1959 -- From the U-2 to the UN Shoe: April-September 1960 -- Khrushchev and Kennedy: 1960-1961 -- "A Communist Society Will be Just about built by 1980": 1961-1962 -- The Cuban Cure-all: 1962 -- The unraveling: 1962-1964 -- After the fall: 1964-1971.
Includes bibliographical references (p. 793-824) and index.
Keywords: Khrushchev, Nikita Sergeevich, -- 1894-1971.; Heads of state -- Soviet Union -- Biography; Soviet Union -- Politics and government -- 1953-1985.